2012
DOI: 10.4103/0972-2327.94992
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, polycystic ovarian syndrome and thyroid dysfunction in women with epilepsy

Abstract: Introduction:Women with epilepsy (WWE) have an increased risk for several endocrine disorders. Obesity and Polycystic Ovarian Syndrome (PCOS) are common side-effects of anticonvulsant drugs.Aim:To study the prevalence of Obesity, PCOS, Thyroid dysfunction in WWE on monotherapy with Carbamazepine (CBZ), Sodium Valproate (VAL) and Phenytoin (DPH)Material and Methods:Sixty WWE in the reproductive age group (13 – 45 yr) who are on atleast 6 months of monotherapy with either CBZ (20) or VAL (20) or DPH (20) are sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…There are previous studies demonstrating neutral effect of CBZ 4 10 19 , PHT 5 15 and LTG 4 19 . However, some studies reported that women on CBZ and LTG had a greater BMI when compared with the control group 15 27 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…There are previous studies demonstrating neutral effect of CBZ 4 10 19 , PHT 5 15 and LTG 4 19 . However, some studies reported that women on CBZ and LTG had a greater BMI when compared with the control group 15 27 .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies 5 15 25 have reported increase in BMI in VPA treated subjects in a range of 2 to 4 kg/m 2 , however, de Vries et al 26 have reported no increase in BMI after VPA treatment. There are previous studies demonstrating neutral effect of CBZ 4 10 19 , PHT 5 15 and LTG 4 19 . However, some studies reported that women on CBZ and LTG had a greater BMI when compared with the control group 15 27 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a study by Ayyagari et al . in the year 2012,[ 7 ] which was performed with an aim of studying the PCOS, overweight, and thyroidal disorders in sixty women with epilepsy, they concluded that disorders in endocrine glands during fertility such as PCOS and hyperprolactinemia increase in epileptic women which is a basis for the occurrence of menstrual disorders, galactorrhea, and hirsutism in these persons. Furthermore, Bauer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, considering the treatment for PCOS, if women treated with VPA are affected with PCOS or its characteristics, they may consider taking drugs to improve the reproductive endocrine phenotype. However, there are several studies [3,18,55] displaying different results. Despite the publication of a paper on a similar topic [25], there has been no new meta-analysis in the last decade to summarize the effects of VPA on reproductive endocrinology as more clinical studies have emerged.…”
Section: Introductionmentioning
confidence: 99%